Implementation of the new DGRh S2e guideline on diagnostics and treatment of adult-onset Still’s disease in Germany - Friedrich, Rhea; Kernder, Anna; Blank, Norbert; Ernst, Diana; Henes, Jörg; Keyßer, Gernot; Klemm, Philipp; Krusche, Martin; Meinecke, Anna; Rech, Jürgen; Schulz, Nils; Schomburg, Dirk; et al. (Zeitschrift für Rheumatologie, 2024)
Background: Adult-onset Still’s disease (AOSD) is a rare autoinflammatory disease. Since it can lead to variable organ involvement, including life-threatening complications, and due to newly available therapeutic approaches, the German Society for Rheumatology and Clinical Immunology (Deutsche Gesellschaft für Rheumatologie und klinische Immunologie; DGRh) issued a newly developed S2e guideline in December 2022. Objective: This study aims to investigate the influence of the new guideline on the diagnosis, management, and outcomes of AOSD. Methods: Retrospective data from 168 patients diagnosed with AOSD between 2007 and 2023 (92 women and 76 men; average age 40.39 years) were captured at nine centers in Germany. Patient characteristics; results of laboratory, physical, and instrumental examinations; and therapeutic regimens were analyzed at three different timepoints. Results: After publication of the German AOSD guideline, the time to diagnosis was shorter (mean before: 18.56 months, mean after: 1.29 months) and fewer complications were recorded, especially with respect to macrophage activation syndrome. Although therapeutic approaches did not change over time, treatment side effects were lower in the recent observation periods. Of note, more patients have been diagnosed with cardiac (19% to 23.1%) and pulmonary (13.8% to 23.1%) manifestations of AOSD in recent years. Conclusion: The new AOSD guideline has contributed to increased disease awareness, with earlier diagnosis and identification of extra-articular organ manifestations. Treatment side effects were less frequent, especially those related to glucocorticoids. However, there is still a need to further improve the management of AOSD.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Arthritis; Autoinflammatory disease; Fever; Macrophage activation syndrome; Retrospective study